2017
DOI: 10.1039/c7ra04102k
|View full text |Cite
|
Sign up to set email alerts
|

Condensed dewdrops self-ejecting on sprayable superhydrophobic CNT/SiO2 composite coating

Abstract: We report a type of novel condensed dewdrops self-ejecting coating from sprayable paint, which was prepared by a self-assembly process of SiO2 nano-particles on hydroxylated carbon nano-tubes with subsequent chemical modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The Cassie state dewdrops are first reported on the top of the carbon nanotube array, in which a subversive character is that these Cassie state dewdrops can spontaneously jump out of the original position after the nucleation, growth, and merging. , This motivates us to increase the long-term condensation heat transfer using a new idea by spontaneously shedding the condensate accumulation . In the past 10 years, this coalescence-induced droplet jumping (CIDJ) effect was successively reported on the superhydrophobic surfaces with various structures. The principle of the CIDJ effect , could be described as follows: in the first step, the Cassie state dewdrops will reduce the contact area between the surface and dewdrop, that is, the tiny adhesion force; when two or more dewdrops merge, the kinetic energy ( E k ) of the jumping dewdrop is provided by a coupling effect relating to E k = E s – E v – E i , where E s is the released surface energy, E v is the viscous flow-induced energy, and E i is the interfacial adhesion-induced energy. Obviously, the CIDJ effect can provide an advantageous way to reduce the condensate accumulation and keep it at a low coverage for a long time, which can avoid the phenomenon of thermal resistance from big droplets, water membranes, water bridges, and frosting/icing. …”
Section: Introductionmentioning
confidence: 99%
“…The Cassie state dewdrops are first reported on the top of the carbon nanotube array, in which a subversive character is that these Cassie state dewdrops can spontaneously jump out of the original position after the nucleation, growth, and merging. , This motivates us to increase the long-term condensation heat transfer using a new idea by spontaneously shedding the condensate accumulation . In the past 10 years, this coalescence-induced droplet jumping (CIDJ) effect was successively reported on the superhydrophobic surfaces with various structures. The principle of the CIDJ effect , could be described as follows: in the first step, the Cassie state dewdrops will reduce the contact area between the surface and dewdrop, that is, the tiny adhesion force; when two or more dewdrops merge, the kinetic energy ( E k ) of the jumping dewdrop is provided by a coupling effect relating to E k = E s – E v – E i , where E s is the released surface energy, E v is the viscous flow-induced energy, and E i is the interfacial adhesion-induced energy. Obviously, the CIDJ effect can provide an advantageous way to reduce the condensate accumulation and keep it at a low coverage for a long time, which can avoid the phenomenon of thermal resistance from big droplets, water membranes, water bridges, and frosting/icing. …”
Section: Introductionmentioning
confidence: 99%
“…Until now, there have been only a few practical products that apply this superhydrophobic surface, although many methods of making superhydrophobic surfaces have been frequently reported over the past few decades. This is primarily a result of the fact that mechanical contact generated under actual environmental conditions tends to damage the surface textures, resulting in a dramatic loss in superhydrophobic properties. …”
Section: Introductionmentioning
confidence: 99%
“…The improved mobility of droplets is demonstrated to successfully enhance the heat transfer characteristics of DWC, particularly when coalescence-induced droplet jumping occurs. 16 However, it is found that a SHPO could impede the nucleation process because according to the nucleation theory, the presence of a large contact angle (CA) elevates the formation energy barrier of a liquid cluster. 17 This problem is particularly serious when the condensation suffers from small subcooling degree and the existence of NCG.…”
Section: Introductionmentioning
confidence: 99%